Design analysis of BRB energy dissipated devices in commercial building structures. (2021) - Chaturvedi, Rishabh; Sharma, Aman; Islam, Anas
Abstract: This paper deals with the study, design and analysis of Buckling Restrained Bracings (BRB) and the also the optimized placings of BRB within the building so as the damage caused by seismic loadings is decreased to a bigger extent. For doing so an analytical study of a G + 7 commercial structure was meted out for the various parameters such as Maximum Story Drift, Maximum Story Displacement, Maximum Story Shear and Maximum Overturning Moment considering the frames without braces (conventional methods), with steel core braces and aluminum core braces (Al-BRB) by using E-tabs for finding the effect of each type of bracing on the parameters. Finally, the results were analyzed for the optimum use of BRB for seismic performance. Based upon the results, it is revealed that the use of steel core BRBs has increased the self – weight of the structure and hence the Light Weight BRB (LWBRB) can be used as an effective alternative for the Steel Core BRB. Ductile material such as Aluminum core can be used as a replacement for the steel core of the BRB. Due to reduced self – weight of the BRB as the section in the Buckling Restrained Braced Frame can be lighter in weight.